2014
DOI: 10.1016/j.ygeno.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Negative energy balance affects imprint stability in oocytes recovered from postpartum dairy cows

Abstract: Ovarian follicle development in post-partum, high-producing dairy cows, occurs in a compromised endogenous metabolic environment (referred to as negative energy balance, NEB). Key events that occur during oocyte/follicle growth, such as the vital process of genomic imprinting, may be detrimentally affected by this altered ovarian environment. Imprinting is crucial for placental function and regulation of fetal growth, therefore failure to establish and maintain imprints during oocyte growth may contribute to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…Using a bovine model, we and others have previously shown that elevated NEFA concentrations during oocyte maturation and embryo culture are detrimental for embryonic development [1, 3]. Additionally, elevated NEFA levels in the oocyte’s microenvironment can affect gene expression, DNA methylation at imprinted genes and alter the phenotype of resultant blastocysts [46]. Lower cell numbers and increased apoptosis were observed in blastocysts after exposure of oocytes to elevated NEFA concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Using a bovine model, we and others have previously shown that elevated NEFA concentrations during oocyte maturation and embryo culture are detrimental for embryonic development [1, 3]. Additionally, elevated NEFA levels in the oocyte’s microenvironment can affect gene expression, DNA methylation at imprinted genes and alter the phenotype of resultant blastocysts [46]. Lower cell numbers and increased apoptosis were observed in blastocysts after exposure of oocytes to elevated NEFA concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Improved energy status in short dry period group will fasten the postpartum ovulation, thus decreasing the service period and increasing reproductive efficiency (De Feu et al 2009). In addition, the total number of services required for conception was more with less insemination success rate in group I, compared to the other two groups indicating reduced quality of oocytes (O'Doherty et al, 2014). dry period (60 or > 60 days).…”
Section: Box Plot Analysismentioning
confidence: 88%
“…Further, it has been well documented that the severity and duration of NEB are positively associated with the interval to first postpartum ovulation. In addition, NEB exerts negative effects on the imprint stability in the oocytes, reducing conception rates during first weeks of the breeding season (O'Doherty et al, 2014). So, a study has been carried out to evaluate the extent of adaptation of high yielding buffaloes to negative energy balance in response to various dry period lengths, by using serum NEFA, ANEFAP levels and days required for postpartum conception as indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Grossniklaus et al, 2013;Heard and Martienssen, 2014;Blake and Watson, 2016). Despite the limited number of epigenetic studies in dairy cattle, they have covered milk production (Singh et al, 2010), reproduction (Sun et al, 2013;Walker et al, 2013;Saadi et al, 2017;O'Doherty et al, 2014), ageing (Green et al, 2015), and health (e.g. Green and Kerr, 2014;Doherty et al, 2016).…”
Section: Methylation and Gene Expression Analysesmentioning
confidence: 99%